Comparative evaluation of curcumin and curcumin loaded- dendrosome nanoparticle effects on the viability of SW480 colon carcinoma and Huh7 hepatoma cells - M.J. Dehghan Esmatabadi; M. Sarkandi; H. Motaleb Zadeh; G. Khaledi; M. Montazeri; H. S. Zahed Shekarabi; Y. Ayoubi Hormoz; E. Ali Asgari (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Colorectal cancer is the third most common cancer and a major cause of morbidity globally. Hepatocellular carcinoma is a leading cause of death in the world. About 80% of all anticancer drugs are somehow related to natural products. One of the most important of these natural compounds is curcumin, the main component of turmeric that has a wide range of pharmacological activities. Curcumin has been found to suppress cell proliferation and decrease cell viability in various types of cancer cells; however, owing to lack of aqueous solubility, curcumin has shown reduced bioavailability in studies. Recent studies have shown that new 400th generation of dendrosome nanoparticle can increase bioavailability of curcumin and thus enhance the cytotoxic properties.  The aim of this study was to determine effectiveness of curcumin alone and in combination with 400th generation dendrosome nanoparticles (DNC) on cell viability rate in SW480 and Huh7 cells. Methods: SW480 and Huh7 cells were incubated with different concentrations of curcumin and DNC (0-50μM) for 24, 48 and 72 h. Then cytotoxicity was assessed by MTT assay and IC50 was determined. Results: The results suggested that the concentration-dependent inhibitory effect of DNC was stronger than curcumin on SW480 and Huh7 cells. Conclusion: The results suggest DNC as a more effective herbal anticancer agent for colorectal and hepatocellular tumors.